Extracellular HMGB1: a therapeutic target in severe pulmonary inflammation including COVID-19? - Ulf Andersson; William Ottestad; Kevin J. Tracey (BMC, 2020)
Abstract Background The 2019 novel coronavirus disease (COVID-19) causes for unresolved reasons acute respiratory distress syndrome in vulnerable individuals. There is a need to identify key pathogenic molecules in COVID-19-associated inflammation attainable to target with existing therapeutic compounds. The endogenous damage-associated molecular pattern (DAMP) molecule HMGB1 initiates inflammation via two separate pathways. Disulfide-HMGB1 triggers TLR4 receptors generating pro-inflammatory cytokine release. Extracellular HMGB1, released from dying cells or secreted by activated innate immunity cells, forms complexes with extracellular DNA, RNA and other DAMP or pathogen-associated molecular (DAMP) molecules released after lytic cell death. These complexes are endocytosed via RAGE, constitutively expressed at high levels in the lungs only, and transported to the endolysosomal system, which is disrupted by HMGB1 at high concentrations. Danger molecules thus get access to cytosolic proinflammatory receptors instigating inflammasome activation. It is conceivable that extracellular SARS-CoV-2 RNA may reach the cellular cytosol via HMGB1-assisted transfer combined with lysosome leakage. Extracellular HMGB1 generally exists in vivo bound to other molecules, including PAMPs and DAMPs. It is plausible that these complexes are specifically removed in the lungs revealed by a 40% reduction of HMGB1 plasma levels in arterial versus venous blood. Abundant pulmonary RAGE expression enables endocytosis of danger molecules to be destroyed in the lysosomes at physiological HMGB1 levels, but causing detrimental inflammasome activation at high levels. Stress induces apoptosis in pulmonary endothelial cells from females but necrosis in cells from males. Conclusion Based on these observations we propose extracellular HMGB1 to be considered as a therapeutic target for COVID-19.